UPAYA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA MELALUI PENDEKATAN SAINS TEKNOLOGI MASYARAKAT PADA SISWA KELAS I SDN 114617 LOBU HUALA - Muriah Sipahutar; Suci Perwita Sari (STKIP Subang, 2026)
This research aims to improve students' motivation to learn mathematics, specifically in addition and subtraction materials with a maximum result of 20, through the implementation of the Science Technology Society (STS) approach. The subjects of this study were 12 first-grade students at SDN 114617 Lobu Huala. This study is a Classroom Action Research (CAR) following the Arikunto model, which consists of two cycles, each including planning, acting, observing, and reflecting. Data on learning motivation were collected through observation sheets covering six indicators: interest in following the lesson, enthusiasm in exploration, courage to ask questions, persistence in completing assignments, group cooperation, and activeness in demonstrating results. The data were analyzed using simple quantitative percentage techniques and qualified based on established criteria. The results showed that the application of the STS approach significantly increased students' learning motivation. This is evidenced by the increase in the average classical percentage of learning motivation from 51.5% (Moderate category) in Cycle I to 83.5% (High category) in Cycle II. This improvement was driven by the use of concrete media from the surrounding environment, which made abstract material more meaningful for students. Based on these results, it can be concluded that the Science Technology Society (STS) approach is an effective solution to enhance learning motivation and the active involvement of first-grade students in mathematics learning